TRANSPLANTATION FOR RENAL AMYLOIDOSIS - KILICTURGAY, S; HABERAL, M (MARCEL DEKKER INC, 1993)
Renal transplantation therapy performed for amyloid nephropathy is controversial because of the fatal effects of the disease. Amyloidosis is a relatively frequent disease and is generally associated with familial Mediterranean fever (FMF) in Turkey. Renal transplantation in the treatment of amyloid nephropathy started in January 1985. Till now, 18 (3.2%) renal transplantations have been performed on patients who had amyloid nephropathy. The mean follow-up period was 34.6 months. Fourteen renal grafts still function well (creatinine: 1-3.2 mg/dL). The overall 1-year patient and graft survival rates were 88.9% and 83.0%, respectively. These rates are not statistically different from renal transplantations done for other cases of renal failure. Therefore, patients with end-stage renal failure due to amyloidosis can be considered as appropriate candidates for renal transplantation.
Keywords: AMYLOIDOSIS; FAMILIAL MEDITERRANEAN FEVER (FMF); RENAL FAILURE; RENAL TRANSPLANTATION; Urology & Nephrology